2015
DOI: 10.1002/14651858.cd009517.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial injury in women undergoing assisted reproductive techniques

Abstract: Analysis 1.2. Comparison 1 Endometrial injury between day 7 of the previous cycle and day 7 of the ET cycle vs control, Outcome 2 Live birth or ongoing pregnancy per randomly assigned woman (by embryo transfer history).. . Analysis 1.3. Comparison 1 Endometrial injury between day 7 of the previous cycle and day 7 of the ET cycle vs control, Outcome 3 Miscarriage per clinical pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(44 citation statements)
references
References 34 publications
0
33
2
9
Order By: Relevance
“…We assumed that if hysteroscopy without biopsy has been found in some studies to lead to increased pregnancy rate, a less invasive procedure like intrauterine saline infusion, which has no adverse effects or does not require anesthesia, may improve implantation in IVF cycles as well ( 14 - 16 ). Contrary to previous results, our study showed that chemical and clinical pregnancy and implantation rates were significantly lower in intervention compared with control group ( 9 - 11 , 18 , 20 , 29 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We assumed that if hysteroscopy without biopsy has been found in some studies to lead to increased pregnancy rate, a less invasive procedure like intrauterine saline infusion, which has no adverse effects or does not require anesthesia, may improve implantation in IVF cycles as well ( 14 - 16 ). Contrary to previous results, our study showed that chemical and clinical pregnancy and implantation rates were significantly lower in intervention compared with control group ( 9 - 11 , 18 , 20 , 29 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent Cochrane's review by Nastri et al it was reported that EI in women undergoing ART between seven days of preceding cycle and the day of ET cycle versus no intervention was associated with increased live birth rate (LBR) in women with more than two previous embryo transfers. These researchers found no evidence regarding the effect of EI on miscarriage, multiple pregnancies or bleeding except mild pain ( 11 ). In another study, endometrial scratching by Pipple twice on day 21 or 22 immediately prior to IVF cycle, had similar LBR compared to the control group, but in a subgroup of patients with two or more previous IVF failures, it improved LBR.…”
Section: Discussionmentioning
confidence: 97%
“…4,5 In the review of 14 studies, LEI was found to be related with an increase in clinical pregnancy rates in women who had two or more ET, while having no effect on incidence of twin pregnancy, miscarriage or bleeding. 15 In the current study, it was found that LEI increased implantation and clinical pregnancy rates in the patients who had their first IVF-ET cycle but this increase was not statistically significant.…”
Section: Discussioncontrasting
confidence: 51%
“…This has been suggested to increase the likelihood of embryo implantation in the subsequent in vitro fertilisation treatment cycle. 26,27 Endometrial injury is not a routine step of outpatient hysteroscopy and could be performed without hysteroscopic guidance. It is plausible that the smaller diameter of the hysterocope used in our study (2•9mm), compared to the diameter of the hysterscopes used in previous studies (5mm), had caused less endometrial surface injury, resulting in a milder degree of endometrial stimulation for implantation.…”
Section: Discussionmentioning
confidence: 99%